Rural education: humanity in school management (Research, Society and Development, 2019)
This article aims to reflect on the education of the Field and humanity in school management addressing issues related to curriculum, human relations and democratic management, seeking the necessary elements to be considered in the school management process, aiming to achieve the democratization and humanization of those involved in the school of the Field. The study is qualitative and the type of research is bibliographical. The collection of data was made in November 2018 in books, articles, monographs, in the repositories of theses and dissertations of the universities referring to the subject studied. It is concluded that School management has an important role for the development of actions aimed at the teaching and learning process, making all involved can be integrated into coherent purposes and according to the context of the community to which they belong , rescuing values, beliefs and the local culture.